2014
DOI: 10.3390/molecules19067223
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Hepatoprotective Activity of Veronica ciliata Fisch. Extracts Against Carbon Tetrachloride-Induced Liver Injury in Mice

Abstract: Veronica ciliata Fisch. has been traditionally used in Traditional Chinese Medicine prescriptions due to its curative effects for hepatitis, cholecystitis, rheumatism, and urticaria. The present study was focused on investigating the role of ethyl acetate and aqueous extracts of Veronica ciliata Fisch. Furthermore, in vitro antioxidant activity (scavenging of DPPH, ABTS, superoxide, and nitrite radicals; reducing power; β-carotene bleaching) and the hepatoprotective effect of the ethyl acetate extract by means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 20 publications
(25 reference statements)
4
18
0
1
Order By: Relevance
“…2 b). This result confirms a previous report [ 9 ]. The analysis of the 9 sub-fractions (A − I) from the EtOAc fraction, showed that Fraction E possessed the greatest antioxidant activity (Fig.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…2 b). This result confirms a previous report [ 9 ]. The analysis of the 9 sub-fractions (A − I) from the EtOAc fraction, showed that Fraction E possessed the greatest antioxidant activity (Fig.…”
Section: Resultssupporting
confidence: 94%
“…The extracts of V. ciliata Fisch. were reported to have strong antioxidant activities and significantly protective effects against acute hepatotoxicity induced by CCl 4 [ 9 ]. Five iridoid glycosides and three derivatives of benzoic acid have been isolated from V. ciliata Fisch.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, GSH combines with harmful substances produced by CCl 4 in the liver and reduces liver damage in order to protect the liver. Previous studies have indicated that GSH may be used to detect the liver damage caused by CCl 4 (23,24). Elevation of TG levels indicated higher fatty acid content, while in a clinical context very high levels of TG are usually associated with liver disease (25).…”
Section: Discussionmentioning
confidence: 99%
“… 1 Toxic chemicals, xenobiotics, alcohol consumption, malnutrition, anemia, medications, autoimmune disorders, and viral infections 2 , 3 are some major causes of liver disease; among which, medications are the most common contributing factors. 4 Drug-induced liver damage accounts for more than 60% of all cases in the United States of America, and it is the leading cause of acute liver failure. 5 …”
Section: Introductionmentioning
confidence: 99%